2008
DOI: 10.1021/nl802011w
|View full text |Cite
|
Sign up to set email alerts
|

Nanofabricated Concentric Ring Structures by Templated Self-Assembly of a Diblock Copolymer

Abstract: The formation of well-controlled circular patterns on the nanoscale is important for the fabrication of a range of devices such as sensors, memories, lasers, transistors, and quantum devices. Concentric, smooth ring patterns with tunable dimensions have been formed from a cylinder-forming poly(styrene- b-dimethylsiloxane) (PS-PDMS) diblock copolymer under confinement in shallow circular trenches. The high etch selectivity between PS and PDMS facilitates pattern transfer, illustrated by the fabrication of array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
151
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 50 publications
5
151
0
Order By: Relevance
“…Spin-coating a film of the block copolymer onto a smooth substrate, then solvent-annealing and etching [25][26][27] (see Supplementary Information for methods) yields oxidized PDMS cylinders with a natural period L o of $35 nm and with varying in-plane orientations as shown in Fig. 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Spin-coating a film of the block copolymer onto a smooth substrate, then solvent-annealing and etching [25][26][27] (see Supplementary Information for methods) yields oxidized PDMS cylinders with a natural period L o of $35 nm and with varying in-plane orientations as shown in Fig. 1.…”
mentioning
confidence: 99%
“…The HSQ posts and native oxide on the silicon wafers were chemically functionalized with a brush layer of PDMS to ensure that the posts had an affinity for the PDMS block of the block copolymer and to improve annealing kinetics. Thin PDMS layers formed at the air and substrate interfaces 3,[25][26][27] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 We previously reported that poly(styrene-b-dimethylsiloxane) (PS-PDMS) diblock copolymers with a large FloryHuggins interaction parameter can generate sub-15-nm wide patterns of 32-40 nm period with excellent long-range ordering and reliability. [12][13][14][15] Our prior work also showed that oxidized PDMS patterns obtained from the BCP can be used as a robust etch mask to pattern soft polymeric films such as a conducting polymer using an oxygen etch 15 and for patterning metal films into dot, ring, line, and antidot arrays. 16,17 (Figures S1 and S2 in the Supporting Information show another example of pattern transfer into a polymer resin.)…”
mentioning
confidence: 97%
“…12-15 Our prior work also showed that oxidized PDMS patterns obtained from the BCP can be used as a robust etch mask to pattern soft polymeric films such as a conducting polymer using an oxygen etch 15 and for patterning metal films into dot, ring, line, and antidot arrays. 16,17 (Figures S1 and S2 in the Supporting Information show another example of pattern transfer into a polymer resin.) In this Letter, we demonstrate transfer of high-quality linear patterns into a variety of metals,…”
mentioning
confidence: 99%